Autoantibody profiles associated with clinical features in psychotic disorders - Jernbom, August; Galletly, Cherrie; Just, David; Toben, Catherine; Baune, Bernhard; Clark, Scott; Liu, Dennis; Nilsson, Peter; Månberg, Anna; Schubert, Oliver (Royal Institute of Technology, 2021)
Dataset from Jernbom Falk, A., Galletly, C., Just, D. et al. Autoantibody profiles associated with clinical features in psychotic disorders. Transl Psychiatry 11, 474 (2021).
Abstract:Autoimmune processes are suspected to play a role in the pathophysiology of psychotic disorders. Better understanding of the associations between auto-immunoglobulin G (IgG) repertoires and clinical features of mental illness could yield novel models of the pathophysiology of psychosis, and markers for biological patient stratification. We undertook cross-sectional detection and quantification of auto-IgGs in peripheral blood plasma of 461 people (39% females) with established psychotic disorder diagnoses. Broad screening of 24 individuals was carried out on group level in eight clinically defined groups using planar protein microarrays containing 42,100 human antigens representing 18,914 proteins. Autoantibodies indicated by broad screening and in the previous literature were measured using a 380-plex bead-based array for autoantibody profiling of all 461 individuals. Associations between autoantibody profiles and dichotomized clinical characteristics were assessed using a stepwise selection procedure. Broad screening and follow-up targeted analyses revealed highly individual autoantibody profiles. Females, and people with family histories of obesity or of psychiatric disorders other than schizophrenia had the highest overall autoantibody counts. People who had experienced subjective thought disorder and/or were treated with clozapine (trend) had the lowest overall counts. Furthermore, six autoantibodies were associated with specific psychopathology symptoms: anti-AP3B2 (persecutory delusions), anti-TDO2 (hallucinations), anti-CRYGN (initial insomnia); anti-APMAP (poor appetite), anti-OLFM1 (above-median cognitive function), and anti-WHAMMP3 (anhedonia and dysphoria). Future studies should clarify whether there are causal biological relationships, and whether autoantibodies could be used as clinical markers to inform diagnostic patient stratification and choice of treatment.

This dataset contains relative continuous as well as binarized autoantibody data, with associated cytokine and clinical data. These data constitute sensitive personal information that fall under the GDPR. Therefore, access to data and related code is restricted. The data can be made available for validation purposes, upon reasonable request and in accordance with GDPR.
A reasonable request should contain:1) Name of PI and host organisation2) Contact details3) Scientific purpose of data access request4) Commitment to inform when the data has been used in a publication5) Commitment not to host or share the data outside the requesting organisation6) Statement of non-commercial use of data
Keywords: Autoimmunity; Psychiatry (incl. psychotherapy); Plant cell and molecular biology; Animal cell and molecular biology; Medical and Health Sciences; Medicin och hälsovetenskap; Molecular Biology; Molekylärbiologi; Psychiatry; Psykiatri; Autoimmunity and Inflammation; Autoimmunitet och inflammation